Nigerian Petroleum Policy and External Relations. - Soremekun, Olukayode (Obafemi Awolowo University, 2014)
This study is on Nigerian Petroleum Policy and External Relations. It utilizes Michael Brecher's theoretical frame -work to analyses the various inter-play of forces in the internal and external environment of the Nigerian petroleum industry. The actors, organs and influences in Nigeria's petroleum. It was revealed that owing to the psychological and sociological dispositions of Nigeria's decision makers, a substantial measure of incoherence exists in the formulation and implementation of petroleum policy in Nigeria.